A Panel Data Model with Generalized Higher-Order Networks Effects - Badi H. Baltagi; Sophia Ding; Peter H. Egger (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Many data situations require the consideration of network effects among the cross-sectional units of observation. In this paper, we present a generalized panel model which accounts for two features: (i) three types of network effects on the right-hand side of the model, namely through weighted dependent variable, weighted exogenous variables, as well as weighted error components, and (ii) higher-order network effects due to ex-ante unknown network-decay functions or the presence of multiplex (or multi-layer) networks among all of those. We outline the model, the basic assumptions, and present simulation results.
Keywords: C23; C33; C34; 330; spatial and network interdependence; panel data; higher-order network effects